Racial and ethnic disparities in childhood and young adult acute lymphocytic leukaemia: secondary analyses of eight Children's Oncology Group cohort trials. Issue 2 (February 2023) - Gupta, Sumit; Dai, Yunfeng; Chen, Zhiguo; Winestone, Lena E; Teachey, David T; Bona, Kira; Aplenc, Richard; Rabin, Karen R; Zweidler-McKay, Patrick; Carroll, Andrew J; Heerema, Nyla A; Gastier-Foster, Julie; et al.
Summary: Background: Previous studies have identified racial and ethnic disparities in childhood acute lymphocytic leukaemia survival. We aimed to establish whether disparities persist in contemporaneous cohorts and, if present, are attributable to differences in leukaemia biology or insurance status. Methods: Patients with newly diagnosed acute lymphocytic leukaemia in inpatient and outpatient centres in the USA, Canada, Australia, and New Zealand, aged 0–30 years, who had race or ethnicity data available, enrolled on eight completed Children's Oncology Group trials (NCT00103285, NCT00075725, NCT00408005, NCT01190930, NCT02883049, NCT02112916, NCT02828358, and NCT00557193 ) were included in this secondary analysis. Race and ethnicity were categorised as non-Hispanic White, Hispanic, non-Hispanic Black, non-Hispanic Asian, and non-Hispanic other. Event-free survival and overall survival were compared across race and ethnicity groups. The relative contribution of clinical and biological disease prognosticators and insurance status was examined through multivariable regression models, both among the entire cohort and among those with B-cell lineage versus T-cell lineage disease. Findings: Between Jan 1, 2004, and Dec 31, 2019, 24 979 eligible children, adolescents, and young adults with acute lymphocytic leukaemia were enrolled, of which 21 152 had race or ethnicity data available. 11 849 (56·0%) were male and 9303 (44·0%) were female. Non-Hispanic White patients comprised the largest racial or ethnic group (13 872 [65·6%]), followed by Hispanic patients (4354 [20·6%]), non-Hispanic Black patients (1517 [7·2%]), non-Hispanic Asian (n=1071 [5·1%]), and non-Hispanic other (n=338 [1·6%]). 5-year event-free survival was 87·4% (95% CI 86·7–88·0%) among non-Hispanic White patients compared with 82·8% (81·4–84·1%; hazard ratio [HR] 1·37, 95% CI 1·26–1·49; p<0·0001) among Hispanic patients and 81·8% (79·3–84·0; HR 1·45, 1·28–1·65; p<0·0001) among non-Hispanic Black patients. Non-hispanic Asian patients had a 5-year event-free survival of 88·1% (95% CI 85·5–90·3%) and non-Hispanic other patients had a survival of 82·8% (76·4–87·6%). Inferior event-free survival among Hispanic patients was substantially attenuated by disease prognosticators and insurance status (HR decreased from 1·37 [1·26–1·49; p<0·0001] to 1·11 [1·00–1·22; p=0·045]). The increased risk among non-Hispanic Black patients was minimally attenuated (HR 1·45 [1·28–1·65; p<0·0001] to 1·32 [1·14–1·52; p<0·0001]). 5-year overall survival was 93·6% (91·5–95·1%) in non-Hispanic Asian patients, 93·3% (92·8–93·7%) in non-Hispanic White patients, 89·9% (88·7–90·9%) in Hispanic, 89·7% (87·6–91·4%) in non-Hispanic Black patients, 88·9% (83·2–92·7%) in non-Hispanic other patients. Disparities in overall survival were wider than event-free survival (eg, among non-Hispanic other patients, the HR for event-free survival was 1·43 [1·10–1·85] compared with 1·74 [1·27–2·40] for overall survival). Disparities were restricted to patients with B-cell acute lymphocytic leukaemia, no differences in event-free survival or overall survival were seen in the T-cell acute lymphocytic leukaemia group. Interpretation: Substantial disparities in outcome for B-cell acute lymphocytic leukaemia persist by race and ethnicity, but are not observed in T-cell acute lymphocytic leukaemia. Future studies of relapsed patients, access to and quality of care, and other potential aspects of structural racism are warranted to inform interventions aimed at dismantling racial and ethnic disparities. Funding: National Cancer Institute and St Baldrick's Foundation.